Adverse Cardiovascular Outcomes and Antihypertensive Treatment: A Genome‐Wide Interaction Meta‐Analysis in the International Consortium for Antihypertensive Pharmacogenomics Studies. Issue 3 (15th August 2021) - McDonough, Caitrin W.; Warren, Helen R.; Jack, John R.; Motsinger‐Reif, Alison A.; Armstrong, Nicole D.; Bis, Joshua C.; House, John S.; Singh, Sonal; El Rouby, Nihal M.; Gong, Yan; Mychaleckyj, Joesyf C.; Rotroff, Daniel M.; et al.
Abstract : We sought to identify genome‐wide variants influencing antihypertensive drug response and adverse cardiovascular outcomes, utilizing data from four randomized controlled trials in the International Consortium for Antihypertensive Pharmacogenomics Studies (ICAPS). Genome‐wide antihypertensive drug‐single nucleotide polymorphism (SNP) interaction tests for four drug classes (β‐blockers, n  = 9, 195; calcium channel blockers (CCBs), n  = 10, 511; thiazide/thiazide‐like diuretics, n  = 3, 516; ACE‐inhibitors/ARBs, n  = 2, 559) and cardiovascular outcomes (incident myocardial infarction, stroke, or death) were analyzed among patients with hypertension of European ancestry. Top SNPs from the meta‐analyses were tested for replication of cardiovascular outcomes in an independent Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) study ( n  = 21, 267), blood pressure (BP) response in independent ICAPS studies ( n  = 1, 552), and ethnic validation in African Americans from the Genetics of Hypertension Associated Treatment study (GenHAT; n  = 5, 115). One signal reached genome‐wide significance in the β‐blocker‐SNP interaction analysis (rs139945292, Interaction P  = 1.56 × 10 −8 ). rs139945292 was validated through BP response to β‐blockers, with the T‐allele associated with less BP reduction (systolic BP response P  = 6 × 10 −4, Beta = 3.09, diastolic BP response P  = 5 × 10 −3, Beta = 1.53). The T‐allele was also associated with increased adverse cardiovascular risk within the β‐blocker treated patients' subgroup ( P  = 2.35 × 10 −4, odds ratio = 1.57, 95% confidence interval = 1.23–1.99). The locus showed nominal replication in CHARGE, and consistent directional trends in β‐blocker treated African Americans. rs139945292 is an expression quantitative trait locus for the 50 kb upstream gene NTM (neurotrimin). No SNPs attained genome‐wide significance for any other drugs classes. Top SNPs were located near CALB1 (CCB), FLJ367777 (ACE‐inhibitor), and CES5AP1 (thiazide). The NTM region is associated with increased risk for adverse cardiovascular outcomes and less BP reduction in β‐blocker treated patients. Further investigation into this region is warranted.